On Using ReSpeaker Mic Array 2.0 for speech processing algorithms - Mischie, Septimiu; Gasparesc, Gabriel (International Symposium on Electronics and Telecommunications (Online), 2020)
The paper presents the structure and applications achieved with a newly launched device called ReSpeaker Mic Array 2.0 (ReSpeaker 2 for short). This is a four microphones array that also contains the XMOS XVF-3000 chipset. This chipset includes many signal and speech processing algorithms. Thus the paper presents applications that mainly use the embedded software of XMOS but also applications that gather the four signals acquired by ReSpeaker 2 and implement the algorithms using another hardware platform. The applications present algorithms such as acoustic echo cancelation, direction of arrival for multiple sources, speech separation and speech to text conversion. ReSpeaker 2 is used with Raspberry Pi or a Personal Computer running Windows or Linux.